Pengadaan Sarana Dan Prasarana Perusahaan Di Kota Megapolitan : (Studi Kasus: PT AMS) - Hasyim Asy'ari; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2024)
This research uses a qualitative description approach, namely describing, analyzing and discussing an existing problem. Qualitative research is based on two data, namely primary and secondary. The purpose of this research is to determine the procurement of existing facilities and infrastructure at PT AMS including the procurement process, availability, and consequences made by the company in procuring facilities and infrastructure. From the results of this research, it can be seen that the facilities and infrastructure at PT AMS are sufficient to accommodate them but improvements are still needed to meet the company's operational standards. This can be overcome by adding facilities according to the company's needs without abandoning existing facility procurement procedures.